Dao-Chi Powder Ameliorates Pancreatitis-Induced Intestinal and Cardiac Injuries via Regulating the Nrf2-HO-1-HMGB1 Signaling Pathway in Rats - Jiaqi Yao; Yifan Miao; Yumei Zhang; Lv Zhu; Huan Chen; Xiajia Wu; Yue Yang; Xiaoyu Dai; Qian Hu; Meihua Wan; Wenfu Tang (Frontiers Media S.A., 2022)
Dao-Chi powder (DCP) has been widely used in the treatment of inflammatory diseases in the clinical practice of traditional Chinese medicine, but has not been used in acute pancreatitis (AP). This study aimed to evaluate the effect of DCP on severe AP (SAP) and SAP-associated intestinal and cardiac injuries. To this end, an SAP animal model was established by retrograde injection of 3.5% taurocholic acid sodium salt into the biliopancreatic ducts of rats. Intragastric DCP (9.6 g/kg.BW) was administered 12 h after modeling. The pancreas, duodenum, colon, heart and blood samples were collected 36 h after the operation for histological and biochemical detection. The tissue distributions of the DCP components were determined and compared between the sham and the SAP groups. Moreover, molecular docking analysis was employed to investigate the interactions between the potential active components of DCP and its targets (Nrf2, HO-1, and HMGB1). Consequently, DCP treatment decreased the serum levels of amylase and the markers of gastrointestinal and cardiac injury, further alleviating the pathological damage in the pancreas, duodenum, colon, and heart of rats with SAP. Mechanistically, DCP rebalanced the pro-/anti-inflammatory cytokines and inhibited MPO activity and MDA levels in these tissues. Furthermore, Western blot and RT-PCR results showed that DCP intervention enhanced the expression of Nrf2 and HO-1 in the duodenum and colon of rats with SAP, while inhibiting the expression of HMGB1 in the duodenum and heart. HPLC-MS/MS analysis revealed that SAP promoted the distribution of ajugol and oleanolic acid to the duodenum, whereas it inhibited the distribution of liquiritigenin to the heart and ajugol to the colon. Molecular docking analysis confirmed that the six screened components of DCP had relatively good binding affinity with Nrf2, HO-1, and HMGB1. Among these, oleanolic acid had the highest affinity for HO-1. Altogether, DCP could alleviated SAP-induced intestinal and cardiac injuries via inhibiting the inflammatory responses and oxidative stress partially through regulating the Nrf2/HO-1/HMGB1 signaling pathway, thereby providing additional supportive evidence for the clinical treatment of SAP.